A Model to Explain the Impacts of Personal Factors on the Acceptance of Mobile Commerce - Abdolmajid Mosleh; Adel Pourdehghan (مطالعات مدیریت کسب و کار هوشمند, 2013)
Today, mobile devices have changed the way of communication and interaction, andhave a strong influence on modern management. It also provides the ability to doeffective work and has created entirely new activities. Currently, developingcountries is a Market that has a grate potential for Telecommunications and manymobile commerce services providers. In this regard, businesses need to focus on thelead to effective results mobile commerce acceptance by customers according totheir needs and tendencies.The aim of this study is to analyze impact of individual drivers on the adoptionof mobile commerce according to TAM model. Research conceptual model wasdeveloped based on theoretical studies and data acquisition was carried out bysurveying of 350 mobile phone users. For data analysis and verification of themodel, structural equation modeling approach (SEM) and confirmatory factoranalysis (CFA) were used.Based on the results of the path analysis the relationship between the variablesin the model is investigated and results suggest that indicators of socialinfluence, innovativeness, compatibility and Individual knowledge have asignificant positive effect on attitude and willingness of users to use mobilecommerce and Leading to the adoption of mobile commerce by users.